An Assessment of the Prevalence of Herbal Medicine Advertisement and Its Effect on Consumers: A Study of Traditional Medicine in Ghana - Arthur, Emmanuel J.K. (UniMAC-GIJ, 2015)
The general objective of this study was to assess the effectiveness of Traditional Medicine advertising on consumer decision-making in Ghana. This study adopted the descriptive survey approach and collected data from 100 customers of five Traditional Medicine Practitioners based in the Greater Accra region. This study found that 75 % of the respondents were generally knowledgeable about traditional medicine, had positive attitudes and perceptions about traditional medicine. The study found that adverts on traditional medicines affect respondents' patronage and usage of traditional medicine. It was specifically found that 70% of the respondents agreed that advertisement of traditional medicines essentially informed them to buy traditional medicine. Factors affecting consumers' buying process include the usefulness, truthfulness and clarity of the messages in the adverts of TMs among others, in the TMAs. Based on these, a number of key recommendations are proffered, one of them being that adverts should be made to follow standards recommended by the Food and Drugs Board. That way, producers of traditional medicines would be seen practicing what they preach. The reality is that "safety" and "natural" are not synonymous. Therefore, regulatory policies on traditional medicines need to be standardized and strengthened on a national scale.
MA Media Studies